Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T18:56:01+01:00
7+(-2) = 7-2=5
(-15)+(-3)=-15-3=-18
(-21)-(-15)=-21+15=-6
(-0,8)-(-0,8)=-0.8+0.8=0
-(¾)+(¼)=-¾+¼=-²/₄
-1,2-[-(-0,8)]=-1.2-0.8=-2
7-(-2)=7+2=9
-(-0,5)-(½)=0.5-½=½-½=0
24-(-15)+(-32) =24+15-32=39-32=7
2009-12-08T18:56:08+01:00
7-2=5
-15-3=-18
-21+15=-6
-0,8+0,8=0
-3/4+1/4=-2/4
-1,2-0,8=-2
7+2=9
0,5-1/2=0,5-0,5=0
24+15-32=39-32=7
2009-12-08T18:58:10+01:00
7+(-2)=7-2=5
(-15)+(-3)=-15-3=-18
(-21)-(-15)=-21+15=-6
(-0,8)-(-0,8)=-0.8+0,8=0
-(3/4)+(1/4)=2/4=1/2
-1,2-[-(-0,8)]=-1,2-0,8=-2
7-(-2)=7+2=9
-(-0,5)-(1/2)=0,5-1/2=0
24-(-15)+(-32)=24+15-32=7